Operating in a Constricted Space: Policy Actor Perceptions of Targeting to Address U.S. Health Disparities. Issue 1 (January 2020) - Grier, Sonya A.; Schaller, Tracey King
Policy actors design and implement targeted interventions to eliminate disparities that exist between groups. Although necessary for achieving health equity, the use of targeting as a policy tool carries the potential for political backlash and social debate, which may influence whether and how policy actors use it. In this research, the authors examine policy actor perceptions regarding the use of targeting in the implementation of health policy. The authors conduct elite interviews with policy actors to better understand their work to design and implement interventions to address health disparities. Findings identify key tensions and trade-offs faced by policy actors related to targeting and reveal sociopolitical influences that shape whether and how targeted programs are considered, who receives them, and by what means they are delivered. The authors discuss the implications of the findings for the use of targeting and related marketing practices by policy actors to address health disparities and other significant public health concerns.